The mighty Red : a novel - Erdrich, Louise (New York, NY : Harper Large Print, 2024)
"Gary Geist, a terrified young man set to inherit two farms, is desperate to marry Kismet Poe, an impulsive, lapsed Goth who can't read her future but seems to resolve his. Hugo, a gentle red-haired, home-schooled giant, is also in love with Kismet. He's determined to steal her and is eager to be a home wrecker. Kismet's mother Crystal hauls sugar beets for Gary's family, and on her nightly runs, tunes into the darkness of late-night radio, sees visions of guardian angels, and worries for the future--her daughter's and her own. Human time, deep time, Red River time, the half-life of herbicides and pesticides, and the elegance of time represented in fracking core samples from unimaginable depths, is set against the speed of climate change, the depletion of natural resources, and the sudden economic meltdown of 2008-2009. How much does a dress cost? A used car? A package of cinnamon rolls? Can you see the shape of your soul in the everchanging clouds? Your personal salvation in the giant expanse of sky? These are the questions the people of the Red River Valley of the North wrestle with every day"--
Keywords: Indians of North America -- Fiction; Human ecology -- Fiction; Global Financial Crisis, 2008-2009 -- Fiction; Love triangles -- Fiction; Man-woman relationships -- Fiction; Climatic changes -- Fiction; Conservation of natural resources -- Fiction; Large type books; Red River Valley (Minn. and N.D.-Man.) -- Fiction; North Dakota -- Fiction